Effect of Maternal Sildenafil Supplementation During Gestation on the Reproductive Performance of Sows/Gilts and Growth Performance of Neonatal Piglets - Wang, Yue; Qin, Yusheng; Zhao, Wei; Yao, Fusheng; Wang, Wenjing; Hu, Xiao; Cheng, Linghua; An, Lei; Tian, Jianhui (Frontiers in Veterinary Science, 2022)
Sildenafil, a phosphodiesterase 5 (PDE-5) inhibitor, provides an alternative and effective strategy to increase uterine blood flow and vascular development, thus improving fetal development. Previous studies have shown that sildenafil attenuates fetal growth restriction in rodents, sheep, and humans. However, the effect of sildenafil intervention on fetal growth in pigs remains unclear. This study aims to evaluate the effect of dietary supplementation with sildenafil on the reproductive performance of sows and gilts. Over 700 Landrace × Large White crossbred sows in the 3rd or 4th parity were randomly assigned to the control group and the sildenafil treatment groups. In brief, sows in the treatment groups were given a basic diet supplemented with sildenafil (0.32 g/day) during different stages of gestation: (1) gestation day (GD) 0–110; (2) GD 0–30; (3) GD 30–80; (4) GD 80–110; and (5) GD 30–110. At parturition, the total number of piglets born per litter, the number of piglets born alive or dead, the average birth weight, the number of weaned piglets, and the average weaning weights were recorded and analyzed. Sildenafil supplementation throughout gestation (GD 0–110) increased both the litter size and the average birth weight. To reduce the cost of extended sildenafil supplementation, time-phased strategies were further tested. Sildenafil supplementation during early gestation (GD 0–30), mid-gestation (GD 30–80), and late gestation (GD 80–110) partially improved litter performance. Notably, sows fed sildenafil supplementation from the mid-to-late gestation period (GD 30–110) showed significantly improved litter performance, approaching the levels in the sows supplemented with sildenafil throughout the whole gestation period. Taken together, our results showed that maternal sildenafil supplementation during gestation can effectively improve the reproductive performance of sows and gilts, and enhance the growth performance of neonatal piglets, thus providing a promising and practical intervention strategy to improve reproductive management in pig farming.